2022
DOI: 10.1021/acsnano.2c09747
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength and Polarization Sensitive Synaptic Phototransistor Based on Organic n-type Semiconductor/Supramolecular J-Aggregate Heterostructure

Abstract: Human retina-and brain-inspired optoelectronic synapses, which integrate light detection and signal memory functions for data processing, have significant interest because of their potential applications for artificial vision technology. In nature, many animals such as mantis shrimp use polarized light information as well as scalar information including wavelength and intensity; however, a spectropolarimetric organic optoelectronic synapse has been seldom investigated. Herein, we report an organic synaptic pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…For molecular thin films and devices, e.g. , for polarization-sensitive photodetectors or phototransistors where strongly polarized J-like optical properties are desired, 69 the twisted “sandwich” structure is a promising candidate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For molecular thin films and devices, e.g. , for polarization-sensitive photodetectors or phototransistors where strongly polarized J-like optical properties are desired, 69 the twisted “sandwich” structure is a promising candidate.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed structure for polymorph B emphasizes that the twisted ''sandwich'' structure is another possible target for crystal engineering in addition to the conventional ''headto-tail'' motif. For molecular thin films and devices, e.g., for polarization-sensitive photodetectors or phototransistors where strongly polarized J-like optical properties are desired, 69 the twisted ''sandwich'' structure is a promising candidate.…”
Section: Molecular Packing Structurementioning
confidence: 99%
“…N-type organic semiconductor materials have also been investigated for neuromorphic OFET devices, and n-type OFET devices are essential for the all-organic complementary circuits [59][60][61]. Xie et al reported an n-type neuromorphic OFET device with the all-solid-state vertical structure, while the PEO/LiClO4 material functioned as the gate dielectric layer and naphthylene-1,4,5,8-tetracarboxylic-diimidethiophene-vinyl-thiophene (NDI-gTVT) as the organic semiconductor layer, whose schematic structure is illustrated as figure 2(b) [60].…”
Section: Single Semiconductor Materials In Ofetmentioning
confidence: 99%
“…To mimic this polarization‐perceptual vision, Kim et al. inserted J‐aggregate PBI‐1 with a supramolecular core–shell structure into the device as a charge‐trapping layer [23] . The liquid‐crystalline J‐aggregate properties induced preferentially oriented OSC film to exhibit both wavelength‐ and polarization‐dependent synaptic properties.…”
Section: Organic Semiconductors (Osc) In Optoelectronic Synapsementioning
confidence: 99%